Language ideologies of lazuri speakers in Turkey - Türk, Gülşah (My University, 2019)
Lazuri from the Eastern Black Sea region of Turkey is listed among the endangered languages in UNESCO Atlas of the World’s Languages in Danger. Despite the lack of census data on the languages spoken by Turkish citizens as their mother tongues, various research estimate a minimum of 20,000 Lazuri speakers in Turkey. While all speakers of Lazuri are bilingual in Turkish, only 5-10% of the proficient Lazuri speakers are children and teenagers (Kutcher, 2008) since there is rapid decrease in intergenerational language transfer, the language is almost non-existent in the public sphere, and its use in the private sphere is mostly limited especially in the urban context. An analysis of both the early examples of language policies by the Late Ottoman Empire and the more systematic policies of the Republic causing monolingualism in Turkish might explain the current situation of languages in Turkey including Lazuri. However, it alone does not help to understand different attitudes towards the language and opposing stances taken in the language revitalization efforts. Language practices do not only change as a result of structural changes but there is also an element of agency. The literature review shows that this aspect has not been studied in the Turkish context yet. Using data from in-depth interviews with Lazuri speakers from different backgrounds and analyzing the data within the sociopolitical and historical context, language ideologies that inform various language practices of Lazuri speakers have been explored. It aimed to understand the opposing positions within the community regarding the future of the language. The main themes that appeared in the narratives were the temporal, spatial, and the affective aspect of language ideologies. This research claims that by understanding these common themes that Lazuri speakers associate with their language, it is possible to understand the power dynamics behind language use.

UNESCO Tehlike Altında Diller Dünya Atlası’nda Lazca ‘kesinlikle tehlike altında’ kategorisinde bulunuyor. Türkiye vatandaşlarının anadillerine yönelik güncel nüfus verisi bulunmasa da çeşitli çalışmalarda Türkiye’de Lazca konuşanların sayısı en az 20.000 tahmin ediliyor. Lazca konuşan herkes Türkçe de konuşabilmektedir fakat Lazca’yı iyi seviyede kullanabilenlerin yalnızca %5-10’u çocuklar ve gençlerden oluşmaktadır. Bunun nedeni nesiller arası dil iletimindeki hızlı düşüş, dilin kamu alanında varlığının bulunmaması ve özellikle kent bağlamında özel alanlarda dahi kullanımının oldukça sınırlı olmasıdır. Dil politikalarına dair erken örneklerin görüldüğü Geç Osmanlı Dönemi ve tek dillilikle sonuçlanan daha sistematik politikaların uygulandığı Cumhuriyet Dönemi’nin incelenmesi Lazca da dahil Türkiye’deki dillerin şu anki durumunu açıklayabilir. Fakat yalnızca bu tarihsel açıklama dile karşı farklı tutumları ve dili canlandırma çalışmalarına yönelik karşıtlıkları anlamaya yardımcı olmaz. Dil edimleri yalnızca yapısal değişikliklerden etkilenmez ve faillik unsurunun da dikkate alınması gerekir. Fakat literatürde Türkiye bağlamında bu unsurun incelendiği bir çalışma bulunmamaktadır. Bu çalışma farklı çevrelerden gelen ve Lazca’yı farklı seviyelerde kullanan kişilerle derinlemesine görüşmeleri, sosyopolitik ve tarihi bağlam içerisinde inceleyerek mevcut dil pratiklerini ve dili canlandırma çalışmalarına yönelik tutumlarını etkileyen dil ideolojilerini analiz etmektedir. Topluluk içerisinde dilin geleceğine yönelik farklı duruşları anlamaya çalışmıştır. Anlatılarda ortaya çıkan temel temalar dil ideolojilerinin zamansal, mekansal ve duygusal yanları olmuştur. Bu araştırma karşılaşılan bu temaları anlayarak dil kullanımının ardındaki iktidar dinamiklerini anlamanın da mümkün olduğunu iddia etmektedir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Lazuri; Language ideologies; Endangered languages; Agency; Lazca; Dil ideolojileri; Tehlike altındaki diller; Faillik